Biograma lietuviškos knygos retrospektyviojoje bibliografijojoje (iki 1940 m.) - Gargasaitė, Dalia (Knygotyra, 1997)
Creation of biograms for the publications of retrospective bibliography is a rather complicated matter. A biogram is composed for the author, compiler, and translator, commencing with the appearance of the first Lithuanian book in 1547 and extending to the present, with the 3rd volume, including the publications of 1905-1917, now in preparation. Encyclopedias and reference books usually contain data only about the most distinguished authors. Thus, authors or translators who have produced one or another minor work often remain unmentioned, and the priority for authorship stays with the compilers of national bibliographies. Information about most of such authors is quite sketchy, and the latest facts might be extremely useful for readers and users when thoroughly selected. Bibliographers should investigate all biographical materials about the author that are available and make precise evaluations regarding these materials. Special attention should be paid to accuracy and reliability. Due to the presentation of misleading dates, the so-called "errors-travelers" might occur, e.g., a case of inaccuracy in the date of birth of the traveler and writer Matas Šalčius. In the description of biograms, the administrative distribution of the definite period of the author’s life should be considered.